2018
DOI: 10.3389/fped.2018.00215
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Milk: Exploring the Linking Ring Among Emerging Components

Abstract: Maternal breast milk (BM) is a complex and unique fluid that evolution adapted to satisfy neonatal needs; in addition to classical nutrients, it contains several bioactive components. BM characteristically shows inter-individual variability, modifying its composition during different phases of lactation. BM composition, determining important consequences on neonatal gut colonization, influences both short and long-term development. Maternal milk can also shape neonatal microbiota, through its glycobiome rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 124 publications
(186 reference statements)
0
32
0
4
Order By: Relevance
“…Furthermore, thanks to this information, it could be possible to modulate infant microbiota, from a protective point of view—especially in preterm neonates, in which the overall immaturity of the organs make them more prone to infections and other diseases, such as NEC and bronchopulmonary dysplasia [25]. In the next five years, this class of nutrient could be the main actor of the tailored nutrition and care of the newborn [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thanks to this information, it could be possible to modulate infant microbiota, from a protective point of view—especially in preterm neonates, in which the overall immaturity of the organs make them more prone to infections and other diseases, such as NEC and bronchopulmonary dysplasia [25]. In the next five years, this class of nutrient could be the main actor of the tailored nutrition and care of the newborn [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides bacteria, their metabolites (e.g., butyrate and other short-chain fatty acids (SCFAs), peptides, oligosaccharides) may also naturally pass into human milk, and this can be detected through metabolomics research using nuclear magnetic resonance spectroscopy [ 63 , 64 ]. Most recently these metabolites have gained more research attention that is focused on their possible role in shaping the growth and development of the infant.…”
Section: Oligosaccharides Bacteria and Microbial Metabolites In mentioning
confidence: 99%
“…The most influential maternal characteristic impacting HMO composition is the expression patterns of Secretor (Se) and Lewis (Le) gene alleles, which code for different fucosyltransferases. Fucosyltransferase 2 (FUT2) is the "secretor" enzyme that transfers fucose residues in α1,2 linkages and fucosyltransferase 3 (FUT3) is the "Lewis" enzyme that transfers fucose residues predominantly as α1,3/4 linkages, leading to different patterns of fucosylated HMOs based on gene expression [8]. Several studies have shown that various environmental factors (geographical location, season of delivery, and maternal diet) [9,10] and maternal characteristics (age, ethnicity, parity, and mode of delivery) [10,11], including pre-pregnancy body mass index (BMI), can also alter HMO composition.…”
Section: Introductionmentioning
confidence: 99%